A cross-layer interference and delay-aware routing metric for multi-radio infrastructure wireless mesh networks. (2018) - Narayan, D.G.; Mudenagudi, Uma
In this paper, we propose new cross-layer interference and delay aware (CL-IDA) routing metric for multi-radio infrastructure wireless mesh networks (WMNs). WMNs use multichannel multiple radio (MCMR) capabilities of mesh routers to achieve high performance. However, QoS degrades significantly due to inter-flow and intra-flow interference as the number of hops and radio interfaces increase. Thus, design of routing protocols combined with routing metrics to improve QoS has become an important research issue. The routing metrics proposed in the literature have their own disadvantages and lack the analytical model in their design. Towards this, we design and implement CL-IDA metric based on the analytical model by estimating delay, inter-flow and intra-flow interference using cross-layer information. We implement this metric using optimised link state routing (OLSR) protocol in NS2. The results reveal that, CL-IDA metric performs better in terms of throughput and average delay compared to well known routing metrics.